Exploring wine knowledge, aesthetics and ephemerality: clustering consumers. Issue 2 (20th June 2016) - Hall, Daniel
Abstract : Purpose: The purpose of this paper is to investigate the relationship between consumer wine knowledge and the aesthetics and ephemerality of wine consumption. Design/methodology/approach: A survey of 254 respondents for questions relating to objective wine knowledge and frequency of wine consumption, as well as the aesthetics and ephemerality of wine consumption was conducted. Clustering analysis was used to produce four discrete consumer clusters that provide insight into Berthon et al. 's (2009) aesthetic and ontology (AO) framework for the consumption of luxury wine brands. Findings: The paper finds that four clusters of wine consumers can be identified that exhibit common characteristics outlined in the AO framework. Practical implications: By clustering consumers and mapping these clusters, the AO framework provides wine marketers with a useful tool to segment the luxury wine market and to develop and deploy tailored wine marketing strategies to target each segment effectively. Originality/value: This study is one of the first to investigate the relationship between consumer wine knowledge, aesthetics and ephemerality. It offers luxury wine marketers useful insights into targeting wine consumers according to their common characteristics.